2022
DOI: 10.3389/fbioe.2022.856745
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of miRNA-TF-mRNA Regulatory Networks in Uterine Fibroids

Abstract: Uterine fibroids (UF) are the most common benign gynecologic tumors and lead to heavy menstrual bleeding, severe anemia, abdominal pain, and infertility, which seriously harm a women’s health. Unfortunately, the regulatory mechanisms of UF have not been elucidated. Recent studies have demonstrated that miRNAs play a vital role in the development of uterine fibroids. As a high-throughput technology, microarray is utilized to identify differentially expressed genes (DEGs) and miRNAs (DEMs) between UF and myometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Given the top three ranking of target drugs for hub DEGs, TOP2A, PLK1, and BIRC5, computational molecular docking was applied to identify the best candidates. As shown in previous studies, irinotecan has the strongest binding to BIRC5 through hydrogen bond formation ( 12 ). In this study, digitoxin and oxytetracycline were found to have the greatest binding affinity for TOP2A and PLK1, respectively.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Given the top three ranking of target drugs for hub DEGs, TOP2A, PLK1, and BIRC5, computational molecular docking was applied to identify the best candidates. As shown in previous studies, irinotecan has the strongest binding to BIRC5 through hydrogen bond formation ( 12 ). In this study, digitoxin and oxytetracycline were found to have the greatest binding affinity for TOP2A and PLK1, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…A PPI network was constructed using the online STRING database ( ) and Cytoscape, as described previously ( 12 ). In addition, hub genes were obtained using molecular complex detection (MCODE) v1.5.1.16 ( 13 ) (degree of cut-off = 2, max.…”
Section: Methodsmentioning
confidence: 99%
“…The predicted binding interaction geometries of ML228 towards HIF1A and staurosporine towards PRKCQ were visualized and the docking affinity was scored. PyMol was applied to visualize the optimal drug-protein conformation as previous described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%